How Meaning of Life Correlates with Emptiness Syndrome of Minangkabau Elderly Women - Arya Fendha Ibnu Shina (IJIP : Indonesian Journal of Islamic Psychology, 2022)
The matrilineal culture in Minangkabau, West Sumatra, is a culture that is thick with emancipation values and the teachings of feminism. The matrilineal kinship system contains the importance of gender equality and justice, both philosophically and in terms of implementation. However, in reality, there has been a shift in the pattern of social responsibility towards women's parents who should have the position of bundo kanduang. The change in the way of social responsibility is marked by the number of parents being put into nursing homes. Psychological conditions related to emptiness syndrome and self-significance in elderly women need to be analyzed. This study involved 40 elderly women who live in social institutions in West Sumatra. This study concluded that there was a significant negative relationship (P value = 0.011) between the meaning of life and emptiness syndrome, which was a -0.396 Pearson correlation.